AN APPRAISAL OF THE NATURE AND SCOPE OF INTERNATIONAL ECONOMIC LAW: CHALLENGES AND NEW DEVELOPMENTS - Oluwadayisi, A. O.; Oke-Samuel, Olugbenga; Jejelola, O. J.; Osamolu, Samuel (IJRDO - Journal of Social Science and Humanities Research, 2017)
International Economic Law comprises of legal studies with a broad collection of laws, regulations and customary practices regulating international trade and business between certain subjects in different nations. This includes the examination of both law and policy on multi-level terms as such private law, local law, national law and international law. It intends to create an understanding of business and economic relations across national frontiers. It expounds the legal problems that transactional economics brings to the fore and makes inquiries into its legal resolution thereof as well as the legal avenues for such resolution. It deals with world’s trade practices in the international sphere while including in them the knowledge and practices of established business touch and emerging practices. This paper seeks to make an overview of the scope and nature of laws that governs the economic relations of states, understanding the concepts, both philosophical and legal, definition of terms and its practical usage and legal framework for international economic law. While examining the legal framework, the sources of international economic law is equally discussed vis-à-vis the impact each source has had on the legal regime of World Economies.